Constructing dual active sites for synergistic electrocatalysis of hydrogen oxidation: single-metal-atoms anchored on WC2O2 MXene. (25th July 2022) - Zhao, Lianming; Han, Xiaonan; Tong, Yanfu; Ding, Yanping; Kong, Weichao; Wang, Jiajun; Li, Bingyu; Xu, Jing; Bai, Peng; Wei, Xing
Abstract : The W2 CO2 MXene-supported single-atom catalysts (W2 CO2 –Msa, Msa = Mn, Fe, Co, Ir, and Pt) show super performance towards the hydrogen oxidation reaction in alkaline media. Abstract : The promising alkaline exchange membrane fuel cells (AEMFCs) are subject to the sluggish kinetics of anodic hydrogen oxidation reaction (HOR). Balancing the adsorption/desorption ability toward H* and OH* is considered to be an efficient way to improve the HOR efficiency, but is extremely hard on one active site. Here, single metal atoms (Msa ) anchored on W2 CO2 MXene (W2 CO2 –Msa ) were built, including a series of 3d, 4d, and 5d metals. First-principles calculations indicate that the charge transfer between Msa and W2 CO2 induces an efficient dual-active site, i.e., Msa as the OH* active site and its adjacent O atoms as the H* active site. The dual active sites on W2 CO2 –Msa can not only avoid the competitive adsorption of H* and OH* but also display a synergistic catalytic effect towards the HOR. Remarkably, W2 CO2 –Msa (Msa = Mn, Fe, Co, Ir, and Pt) shows both high stability and superior HOR activity over bulk Pt, suggesting their huge potential as anodic electrocatalysts for AEMFCs.